Fluids & electrolytes made incredibly easy! (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
Throughout Fluids & Electrolytes Made Incredibly Easy, Fifth Edition, you'll encounter these helpful features that enhance your learning: Clearly written text that focuses precisely on what you need to know; Hundreds of easy-to-understand charts and illustrations; Lighthearted tone that makes learning enjoyable; That's a warp quick reviews of chapter essentials. This one-of-a-kind reference contains all of the information you need to put everything into perspective and improve your patient care. You'll find clear, concise explanations of: Major imbalances, such as dehydration, hypovolemial water intoxication; sodium, calcium, phosphorous, and chloride imbalances; and metabolic respiratory acidosis and alkalosis; Causes, signs and symptoms, treatments, interventions, documentation, and patient teaching
Balancing fluids -- Balancing electrolytes -- Balancing acids and bases -- When fluids tip the balance -- When sodium tips the balance --When potassium tips the balance -- When magnesium tips the balance -- When calcium tips the balance -- When phosphorus tips the balance -- When chloride tips the balance -- When acids and bases tip the balance -- Heat-related illnesses -- Heart failure -- Respiratory failure -- Excessive GI fluid loss -- Acute pancreatitis -- Renal failure -- Burns -- I.V. fluid replacement -- Total parenteral nutrition
Includes bibliographical references and index
13
Keywords: Body fluid disorders -- Nursing; Water-electrolyte imbalances -- Nursing